2015
DOI: 10.1080/1360080x.2015.1019121
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ perceptions of email communication, volume and management strategies in an Australian university

Abstract: Despite email playing a central role in university business, little is known about the strategies used by staff to manage email and the factors contributing to email overload. In a mixed method study undertaken in one Australian university comparing academic (n = 193) and professional (n = 278) staff, we found that while email volume was higher in academics they used fewer email management strategies. For both groups, thematic analyses of commentary responses revealed that the unnecessary use of emails by staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…In terms of contemporary hazards to wellbeing, there is growing evidence that email has become a significant source of stress for university staff. Pignata et al (2015) found that perceptions of overload were commonplace and underpinned by overuse of email by staff and students and expectations for a rapid response. The ability to access emails outside 'standard' working hours can also compound the negative impact of work overload among academics, especially where job involvement is high and boundaries between work and personal life are flexible and permeable (Kinman, 2016).…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…In terms of contemporary hazards to wellbeing, there is growing evidence that email has become a significant source of stress for university staff. Pignata et al (2015) found that perceptions of overload were commonplace and underpinned by overuse of email by staff and students and expectations for a rapid response. The ability to access emails outside 'standard' working hours can also compound the negative impact of work overload among academics, especially where job involvement is high and boundaries between work and personal life are flexible and permeable (Kinman, 2016).…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…Pignata et al (2015) cite a range of papers recording factors associated with email use that lead to workplace stress, including its disruptive nature and the use of excessive monitoring. The authors' own investigation into pressure points highlights not only volume but also issues to do with unnecessary emails and expectations of quick responses.…”
Section: Email's Development In a Neoliberal Contextmentioning
confidence: 99%
“…There is already some literature on overload from email both in business and in academic life. Pignata et al (2015) cite a range of papers recording factors associated with email use that lead to workplace stress, including its disruptive nature and the use of excessive monitoring. The authors' own investigation into pressure points highlights not only volume but also issues to do with unnecessary emails and expectations of quick responses.…”
Section: Email's Development In a Neoliberal Contextmentioning
confidence: 99%